2015
DOI: 10.25103/jestr.082.26
|View full text |Cite
|
Sign up to set email alerts
|

A Memristor - Based Hyperchaotic System with Hidden Attractors : Dynamics , Synchronization and Circuital Emulating

Abstract: Memristor-based systems and their potential applications, in which memristor is both a nonlinear element and a memory element, have been received significant attention recently. A memristor-based hyperchaotic system with hidden attractor is studied in this paper. The dynamics properties of this hyperchaotic system are discovered through equilibria, Lyapunov exponents, bifurcation diagram, Poincaré map and limit cycles. In addition, its anti-synchronization scheme via adaptive control method is also designed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Subsequent studies of this work will consider more aspects for chaos based secure communication, utilizing systems with hidden attractors. These include systems of higher dimension, hyperchaotic systems [15,22], and discrete time systems [69,70]. Also, the transmission of different types of signals, for example for image transmission will also be considered, and also the nonlinear transmission of the information signal.…”
Section: Conclusion and Future Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies of this work will consider more aspects for chaos based secure communication, utilizing systems with hidden attractors. These include systems of higher dimension, hyperchaotic systems [15,22], and discrete time systems [69,70]. Also, the transmission of different types of signals, for example for image transmission will also be considered, and also the nonlinear transmission of the information signal.…”
Section: Conclusion and Future Aspectsmentioning
confidence: 99%
“…Over the years, chaos synchronization has found applications in many scientific disciplines, including, but not limited to, encryption and secure transmission [2][3][4][5][6][7][8], optics and lasers [9,10], engineering [11] and robotics [12][13][14]. So far, a wide variety of design approaches have been applied for synchronization [2,[15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…There are examples of memristorbased chaotic oscillators [10][11][12][13] and Hamiltonian systems including the memristor [14]. A variety of the effects in memristor oscillators is complemented by the existence of hidden attractors [15][16][17] and manifolds of equilibria (in the simplest case it is a line of equilibria) in the phase space [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Buscarino et al [16] introduced a new chaotic oscillator-based HP memristor model; they produced new chaotic signals by using the HP memristor model. Pham et al [17] suggested an adaptive synchronization scheme for a memristor hyper-chaotic system in which an adaptive control method is used for designing an anti-synchronization scheme for the memristor system. The Arduino microcontroller has also been used to implement and develop the chaotic memristor system as in [18].…”
Section: Introductionmentioning
confidence: 99%